2014
DOI: 10.1021/jp506412r
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical, Spectroscopic, and1O2Sensitization Characteristics of 10,10-Dimethylbiladiene Complexes of Zinc and Copper

Abstract: The synthesis, electrochemistry, and photophysical characterization of a 10,10-dimethylbiladiene tetrapyrrole bearing ancillary pentafluorophenyl groups at the 5- and 15-meso positions (DMBil1) is presented. This nonmacrocyclic tetrapyrrole platform is robust and can serve as an excellent ligand scaffold for Zn2+ and Cu2+ centers. X-ray diffraction studies conducted for DMBil1 along with the corresponding Zn[DMBil1] and Cu[DMBil1] complexes show that this ligand scaffold binds a single metal ion within the tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 63 publications
(109 reference statements)
0
54
0
Order By: Relevance
“…Figure 2 compares the cyclic voltammograms obtained for 1.0 mM solutions of Pd [ DMBil1 ] and Pt [ DMBil1 ] with those obtained previously for Zn [ DMBil1 ] and the free base DMBil1 . 25 DPVs recorded for Pd [ DMBil1 ] and Pt [ DMBil1 ] are reproduced in the Supporting Information (Figure S3), and the apparent redox potentials for each of these four compounds are listed in Table 3. All four biladiene derivatives show two 1e − reductions and two 1e − oxidations which are reported versus Ag/AgCl.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 2 compares the cyclic voltammograms obtained for 1.0 mM solutions of Pd [ DMBil1 ] and Pt [ DMBil1 ] with those obtained previously for Zn [ DMBil1 ] and the free base DMBil1 . 25 DPVs recorded for Pd [ DMBil1 ] and Pt [ DMBil1 ] are reproduced in the Supporting Information (Figure S3), and the apparent redox potentials for each of these four compounds are listed in Table 3. All four biladiene derivatives show two 1e − reductions and two 1e − oxidations which are reported versus Ag/AgCl.…”
Section: Resultsmentioning
confidence: 99%
“…DMBil1 and Zn [ DMBil1 ] can sensitize 1 O 2 with quantum yields of Φ Δ < 5%; 25 however, the evidence of a heavy atom effect imparted by the presence of the Pd II and Pt II centers of Pd [ DMBil1 ] and Pt [ DMBil1 ] ( vide supra ) suggested that these two complexes may be more efficient photosensitizers for 1 O 2 production. These hopes were buoyed by the observation that phosphorescence of Pd [ DMBil1 ] and Pt [ DMBil1 ] is actively quenched in the presence of oxygen.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pd[DMBil1]-PEG 750 was synthesized using methods described previously [ 28 , 38 , 39 , 40 , 41 ]. Reactions requiring an inert atmosphere were carried out in oven-dried round bottomed flasks fitted with Suba-seal rubber septa purchased from Chemglass and maintained under positive nitrogen pressure using standard schlenk techniques.…”
Section: Methodsmentioning
confidence: 99%